Estimating the Collapse Point of a Transmission Line in a Developing Power Systems - Onah, J. N.; Onyishi, D. U.; Eze, C. C.; Ogbahor, G. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The trouble with a developing national grid is compounded by the fact that the power system supplies power to a vast number of loads which is fed by a number of generating units sometimes far from the load centers. Variations of loads bring about power losses and corresponding increase in the reactive power requirements of the transmission systems. Thus, the paper is aimed at establishing the point of collapse of transmission lines to enable a control system operator to take proactive measures in the event of small/large system disturbances. Voltage collapse proximity indicator is exploited to show that the variations in load close to the maximum load require extremely large amounts of reactive power at the sending end in order to support the increase in load. In the work, it was identified that Katemkpe-Shiroro transmission line is the most critical transmission line contributing immensely for voltage collapse scenarios in Nigeria national grid. Consequently, it ranked first because it has the highest voltage collapse proximity index. Computation involving voltage collapse proximity indicator obtained the collapse point or the knee point as 2.8684. This serves as a criterion that will enable control system expert to take proactive measure before the impending voltage collapse.